Laparoscopic Cholecystectomy in Patients with Emphysematous and Gangrenous Cholecystitis: An Experience at Khwaja Yunus Ali Medical College & Hospital, Enayetpur, Sirajgonj. - Hossain, Mohd Farid; Biswas, Sailendra Nath; Rahman, Masudur; Ahmed, Tanvir; Karmaker, Apu (KYAMC Journal, 2017)
Objective- To look for the feasibility and safety of laparoscopic cholecystectomy in patients with emphysematous and gangrenous cholecystitis. Back ground- Emphysematous and gangrenous cholecystitis are severe form of acute cholecystitis. They are considered as contraindication of laparoscopic cholecystectomy due to peri operative life threatening complications, surgical technical difficulties, frequent conversion to open procedure. This study describe our experience in terms of feasibility and safety with laparoscopic cholecystectomy in patients with emphysematous and gangrenous cholecystitis. Materials and methods- From January 2012 to December 2014,total 37 patients with clinical diagnosis of severe acute cholecystitis under went laparoscopic cholecystectomy within 72 hours of admission. Operative findings and histopathological reports were used to identify patients of emphysematous and gangrenous cholecystitis. Results- 35(94.59%)among 37 patient's laparoscopic cholecystectomy were performed successfully.29 case were emphysematous and 8 cases were gangrenous cholecystitis. Two patient's laparoscopic procedure were converted to open procedure due to various operative difficulties, of which the most common was distorted calot's triangle. Maximum operating time was up to 130 minutes(one case),Post operative major complications occurred in 2 cases(5.40%).maximum patients were discharged by 48 to72 hours. There was no mortality. Conclusion- laparoscopic cholecystectomy is feasible and safe in emphysematous and gangrenous cholecystitis. However the experience of the surgeon and his patience during surgery play key role in over all out come. Based on our experience we recommend an early laparoscopic cholecystectomy for these group of patients, provided expertise & gadgets are available. KYAMC Journal Vol. 5, No.-2, Jan 2015, Page 519-523